The Chinese Version of the Patient Education Materials Assessment Tool for Printable Materials: Translation, Adaptation, and Validation Study - Yi Shan; Meng Ji; Zhaogang Dong; Zhaoquan Xing; Ding Wang; Xiangting Cao (JMIR Publications, 2023)
BackgroundProviding people with understandable and actionable health information can considerably promote healthy behaviors and outcomes. To this end, some valid and reliable scales assessing the patient-friendliness of health education materials, like the PEMAT-P (Patient Education Materials Assessment Tool for printable materials), have been well developed in English-speaking countries. However, the English version of the PEMAT-P has not been translated and adapted into simplified Chinese and validated in mainland China. ObjectiveThis study sought to translate the PEMAT-P tool into a simplified Chinese (Mandarin) version (C-PEMAT-P, a Chinese version of the Patient Education Materials Assessment Tool for printable materials) and verify its validity and reliability for assessing the comprehensibility and actionability of health education resources written in simplified Chinese. As a result, the validated C-PEMAT-P could be used to guide health researchers and educators to design more comprehensible and actionable materials for more tailored and targeted health education and interventions. MethodsWe translated the PEMAT-P into simplified Chinese in the following three steps: (1) forward-translating the PEMAT-P into simplified Chinese, (2) back-translating the simplified Chinese version into English, and (3) testing translation equivalence linguistically and culturally by examining the original English version of the PEMAT-P and the back-translated English version of the tool. Any discrepancies between the original English tool and the back-translated English tool were resolved through a panel discussion among the research team of all authors to produce a revised forward-translated Chinese version (C-PEMAT-P). We then evaluated the clarity of construction and wording as well as the content relevance of the C-PEMAT-P using a 4-point ordinal scale to determine its content validity. After that, 2 native Chinese speakers (health educators) used the C-PEMAT-P to rate 15 health education handouts concerning air pollution and health to validate their reliability. We calculated the Cohen coefficient and Cronbach α to determine the interrater agreement and internal consistency of the C-PEMAT-P, respectively. ResultsWe finalized the translated Chinese tool after discussing the differences between the 2 English versions (original and back-translated) of the PEMAT-P, producing the final Chinese version of the PEMAT-P (C-PEMAT-P). The content validity index of the C-PEMAT-P version was 0.969, the Cohen coefficient for the interrater scoring agreement was 0.928, and the Cronbach α for internal consistency was .897. These values indicated the high validity and reliability of the C-PEMAT-P. ConclusionsThe C-PEMAT-P has been proven valid and reliable. It is the first Chinese scale for assessing the comprehensibility and actionability of Chinese health education materials. It can be used as an assessment tool to evaluate health education materials currently available and a guide to help health researchers and educators design more comprehensible and actionable materials for more tailored and targeted health education and interventions.